Pengaruh Kecerdasan Emosional, Perilaku Koqnitif, Kemampuan Personal dan Kompetensi Kepemimpinan Terhadap Kinerja Koperasi di Provinsi Aceh - Syamsul Rizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
This study was conducted to investigate the Emotional Intelligence, Behavior Koqnitif, Personal Capability, Competence Leadership and Leadership Performance Leadership Cooperative to Cooperative Performance in Aceh province. This study will explore the four (4) aspects which include; Koqnitif (Coqnitive Behavior), Functional Role (Functional roles), Capability Personal (Personal capabilities) and Kentrampilan Personal (Personal skill). The population in this study are all cooperatives in the province. The population in this research were 207 people (Cooperative) include all cooperatives in the province of Aceh.